2017
DOI: 10.18632/oncotarget.14776
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide screen identifies a novel prognostic signature for breast cancer survival

Abstract: Large genomic datasets in combination with clinical data can be used as an unbiased tool to identify genes important in patient survival and discover potential therapeutic targets. We used a genome-wide screen to identify 587 genes significantly and robustly deregulated across four independent breast cancer (BC) datasets compared to normal breast tissue. Gene expression of 381 genes was significantly associated with relapse-free survival (RFS) in BC patients. We used a gene co-expression network approach to vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 59 publications
(53 reference statements)
1
16
0
Order By: Relevance
“…4). LPAR6 is highly expressed in the liver and HCC (12,42) and has been shown to support liver tumorigenesis (42). LPAR6 is also the highest expressing LPAR in the lung (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…4). LPAR6 is highly expressed in the liver and HCC (12,42) and has been shown to support liver tumorigenesis (42). LPAR6 is also the highest expressing LPAR in the lung (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This contributes to the increase in LPA concentrations in the tumors [110][111][112]. Low LPP1 mRNA expression (PLPP1) is one of 12 changes in mRNA that predicts poor survival in breast cancer patients [113]. We showed that increasing the low levels of LPP1 in breast cancer cells decreases cell division and blocks tumor growth and metastases in a mouse breast cancer model bỹ 80% [27].…”
Section: Effects Of Lpp Expression In Cancersmentioning
confidence: 95%
“…The expressions of these two LPPs are decreased in lung, ovarian, and breast tumors [ 97 , 98 , 99 ] and this can contribute to the increase of LPA concentrations in the tumors [ 100 , 101 , 102 ]. Low expression of mRNA for LPP1 is one of 12 changes in mRNA that predicts poor survival in breast cancer patients [ 103 ]. We showed that mRNA concentrations for LPP1 were lower in all types of breast tumors compared to normal breast tissue [ 27 , 51 ].…”
Section: Role Of Lipid Phosphate Phosphatases In Controlling Lpa Smentioning
confidence: 99%